Створення калькулятору з дискретної математики - Щоголєв, С. А.; Назарько, Д. О. (ХНУРЕ, 2022)
During studying students often have to do routine work while doing homework or during practical classes and tests. Performing the same tasks each time sharpens skills and improves students' knowledge, but does not teach something new. In order to solve more complex task often you need to perform a few easy but time-consuming actions. What's the point of doing all of those when you can use a calculator and quickly move on to the main task? We have presented the solution to this problem in the form of a web application: a calculator in Discrete Mathematics, which includes a calculator in Set algebra and Boolean algebra.
Keywords: калькулятор; дискретна математика